Implementasi Metode PCQ – Queue Tree Pada Router Mikrotik Untuk Meningkatkan Quality Of Service Jaringan Internet Di Desa Renah Semanek - AR Walad Mahfuzi; Dedy Abdullah; Ujang Juhardi; Marhalim Marhalim; Raymond Pallas (Jurnal Media Infotama, 2023)
Abstract_Bandwidth management is a network management technique in an effort to provide fair and satisfactory network performance, which regulates computer networks so that bandwidth is used optimally and evenly. The internet network located in Renah Semanek Village has problems such as unstable internet connection, unequal internet distribution, making it difficult for everyone to access the internet. This study aims to stabilize the internet connection by dividing the maximum possible bandwidth across all clients, so that users will get an equal amount of bandwidth. This implementation has been tested and proven to improve Quality of Service (QoS) on Rt Rw Net. The results of the implementation of the PCQ-Queue Tree method get an increase in QoS value seen from the upload and download parameter testing, initially the internet connection was not divided equally.